Perancangan Buku Cerita Legenda Tiongkok Air Mata Putri Meng Jiang - Jason Kristanto; Ayyub Anshari Sukmaraga (Citradirga : Jurnal Desain Komunikasi Visual dan Intermedia, 2021)
Based on research, Indonesians have a low interest in reading books and there is still a representation of the Chinese generation's culture and also reducing the lessons of character toward children, so theres a need for Chinese folklore story book. The used story is "Princess Meng Jiang" from Zuo's Interpretation set in Qin Dynasty (221-206 BC). This research method uses qualitative methods and Narrative Qualitative research strategies, so as to produce a picture of a story book that introduces the culture and history of the future state of the Qin Dynasty. The design story has the aim to visualized the legendary story of "Princess Meng Jiang" in the form of story books accompanied by minigames and infographic videos, so that children are not involved in reading alone, but also increase knowledge. The design is accompanied by supporting media such as video teasers, Instagram Feeds, infographic videos, posters, flyers, emoji stickers, Instagram filters and merchandise like mugs and bookmarks.